Reinterpreting the Role of Teachers in the Digital Education Era: Between Technological Challenges and Humanistic - Yuni Kasih Purba; Graciella Yoseppin; Johanes Herlijanto (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This study aims to analyze how digital technologies and artificial intelligence (AI) have transformed teachers’ roles in contemporary educational environments. Methodology: A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Twenty-nine articles published between 2020 and 2025 were selected from the Scopus database and analyzed using qualitative synthesis and VOSviewer bibliometric mapping. Main Findings: The findings indicate that teachers are transitioning from traditional knowledge transmitters to facilitators, mentors, learning designers, and ethical guides. Although AI can support instructional tasks such as assessment, content generation, and personalized learning, it cannot fully replace the emotional, ethical, and interpersonal dimensions of teaching. The study also identifies major challenges, including digital competency gaps, unequal technological access, and ethical concerns associated with AI integration. Novelty/Originality of this study: This study contributes a comprehensive understanding of teacher role transformation by integrating findings from recent literature with Social Role Theory. The results emphasize that the future of education depends on balancing technological innovation with human-centered values, highlighting the continuing importance of teachers’ empathy, ethical judgment, and emotional support in AI-enhanced learning environments.